2011
DOI: 10.7589/0090-3558-47.3.745
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Trichinella spp. in Black Bears, Grizzly Bears, and Wolves in the Dehcho Region, Northwest Territories, Canada, Including the First Report of T. nativa in a Grizzly Bear from Canada

Abstract: ABSTRACT:Samples of muscle from 120 black bears (Ursus americanus), 11 grizzly bears (Ursus arctos), and 27 wolves (Canis lupus) collected in the Dehcho Region of the Northwest Territories from 2001 to 2010 were examined for the presence of Trichinella spp. larvae using a pepsin-HCl digestion assay. Trichinella spp. larvae were found in eight of 11 (73%) grizzly bears, 14 of 27 (52%) wolves, and seven of 120 (5.8%) black bears. The average age of positive grizzly bears, black bears, and wolves was 13.5, 9.9, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 11 publications
1
14
0
Order By: Relevance
“…Our estimate of a mean 35 LPG for grizzly bears is also the highest of all reported studies in North America. We did not find a significant relationship between age and LPG in either species, similar to the results of Larter et al (2011), although we did find a trend toward younger bears of both species having higher larval burdens than older bears. Younger animals in a population might have higher parasite burdens because of induction of less effective specific immunity during initial infection, compared with re-exposure or superinfection, or lower innate resistance to infection (Davies et al 2008).…”
supporting
confidence: 76%
See 2 more Smart Citations
“…Our estimate of a mean 35 LPG for grizzly bears is also the highest of all reported studies in North America. We did not find a significant relationship between age and LPG in either species, similar to the results of Larter et al (2011), although we did find a trend toward younger bears of both species having higher larval burdens than older bears. Younger animals in a population might have higher parasite burdens because of induction of less effective specific immunity during initial infection, compared with re-exposure or superinfection, or lower innate resistance to infection (Davies et al 2008).…”
supporting
confidence: 76%
“…The highest recorded prevalence is 12% in the Kootenay region of British Columbia (Schmitt et al 1978). In the Northwest Territories, Larter et al (2011) and Johnson et al (2013) report a prevalence of 5.8%. Our 20% prevalence in black bears was the highest reported in Canada, although our sample size is small.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Studies, however, have shown that not all species of Trichinella are sensitive to cold temperatures. In fact, T. spiralis larval worms are neutralized by freezing the pork either 20 days at À15 °C or 3 days at À20 °C [10,12,29]. In contrast, other species found in wild boars, such as T. britovi and T. nativa, are able to resist cold temperatures [10,12,21,29].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, T. spiralis larval worms are neutralized by freezing the pork either 20 days at À15 °C or 3 days at À20 °C [10,12,29]. In contrast, other species found in wild boars, such as T. britovi and T. nativa, are able to resist cold temperatures [10,12,21,29]. To kill the encysted larvae, internal meat temperatures must reach 62 °C or more, taking into consideration the variability in heat distribution and cooking techniques [6].…”
Section: Discussionmentioning
confidence: 99%